Data analysis of students who used the MAZK Intelligent Tutor System during the pandemic period - Pozzebon , Eliane; Canal , Felipe Zago; Silva , Raissa; de Oliveira , Susi Machado (Seven Editora, 2023)
In this article, we present an analysis of data from an Intelligent Tutor System (ITS) created by a group of Brazilian researchers. The STI was used by approximately 19,000 users from elementary to higher education in public schools. The research methodology used was quantitative and qualitative exploratory analysis. The data set for this study was obtained through the students’ interactions with the STI during remote teaching. In the data analysis, information from the students’ profiles (age, frequency of access, etc.) and interactions were used, for example, the exercises were solved with objective and descriptive questions to identify the student’s abilities and challenges. A total of 2,514,219 responses were analyzed in the STI until 05/31/2021, with 1,533,946 answers to objective questions and 980,273 answers to discursive questions. In the results, it was possible to observe a tendency towards the mastery of mathematics and languages and an excellent performance in 69% of the total answers, which obtained maximum scores in the questions. DOI:https://doi.org/10.56238/emerrelcovid19-053